The effects of acute hyperglycemia on oxidative stress and nitric oxide bioavailability in platelets - ŞENER, AZİZE (AVES PRESS LTD, 2015)
Objective: Platelet activation and thrombus formation tendency increase in diabetes mellitus. Nitric oxide (NO) synthesized by platelets plays important role in platelet functions and limits the recruitment of new platelets to the platelet-rich thrombus. However, NO may also be deleterious by elevating oxidative/nitrosative stress in cells. The aim of the present study was to examine effects of acute high glucose in both resting and collagen-stimulated platelets on platelet aggregation, oxidative stress and NO bioavailability. In addition, we investigated the role of superoxide production on NO bioavailability using quercetin as scavengers of superoxide anion. Methods: Washed platelets were incubated with 5mM D-glucose (physiological concentration, n:7) or 25mM D-glucose (pathophysiological concentration, n:7) or quercetin (10 mu M) plus 25 mM D-glucose (n:7) for 1 h. Superoxide production, lipid peroxidation (LPO), NO, nitrotyrosine (NT) levels and advanced glycation end products (AGE) in platelets were measured after incubation. Platelet aggregation was also investigated. Results: Incubation of resting and collagen-activated platelets with high glucose resulted in significant elevations in LPO, NT and AGE levels when compared to 5mM glucose concentration (p<0.05). High glucose significantly increased platelet aggregation, superoxide formation and NO levels in collagen-activated platelets (p<0.05). Quercetin markedly increased production and bioavailability of NO and suppressed oxidative stress in high glucose incubated platelets (p<0.05). Conclusion: High glucose increases oxidative stress and reduces bioavailability of NO in resting and especially collagen activated platelets. Hyperglycemia mediated superoxide production could be taken part on these effects. These findings would be suggested that there might be beneficial effects of quercetin in the prevention of platelet-related complications in diabetes mellitus.
Keywords: Hyperglycemia; quercetin; collagen; nitric oxide; superoxide anion; platelet